THE EFFECTIVENESS OF AL -WASLI ENRICHMENT IN OBTAINING THE HISTORY SUBJECT OF THE FIRST STUDENTS IS AVERAGE AND THE DEVELOPMENT OF THEIR MORAL VALUES (American Journal of Research in Humanities and Social Sciences, 2023)
The aim of the current research is to identify (the effect of the strategy of instrumental enrichment in the collection of history among first-grade intermediate students and the development of their moral values) The sample of the current research consisted of (60) students from the first grade students, and they were divided randomly into two groups. The two research tools were prepared by the researcher, as the first tool consisted of (50) items, and the second tool was the measure of moral values, and it consisted of (60) items. The researcher made sure of the honesty and consistency of both tools.